Drought Level Analysis of Paddy Fields Using the NDDI Method Based on Sentinel-2A Imagery in South Polombangkeng District, Indonesia - Nur Rahmi; Husnul Mubarak; Sitti Nur Faridah; Muhammad Tahir Sapsal (Program Studi Teknik Pertanian Universitas Hasanuddin, 2025)
Drought is a significant climate-related hazard that severely impacts agricultural productivity, particularly in rainfed paddy fields. This study aimed to analyze the spatial distribution and severity of drought in paddy fields using the Normalized Difference Drought Index (NDDI) derived from Sentinel-2A satellite imagery. The research was conducted in South Polombangkeng District, Takalar Regency, South Sulawesi, Indonesia, during the dry season in October 2023. The NDDI was calculated by integrating the Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Water Index (NDWI). The results indicated that 85.78% of the paddy fields experienced severe drought, while mild and moderate drought covered 9.30% and 4.92%, respectively. NDVI analysis revealed that 87.81% of the area had very low to low vegetation density, and NDWI confirmed extreme moisture deficiency, with 99.88% of the area under very severe drought conditions. The accuracy of the NDDI drought map, validated using the Area Under the Curve (AUC), was 0.62, indicating acceptable model performance. These findings provide critical spatial information for drought mitigation and water management in vulnerable agricultural regions. The study demonstrates the utility of Sentinel-2A and NDDI for localized drought assessment and supports evidence-based decision-making for sustainable farming practices in drought-prone areas.